A Reading-Writing Assignment Based on Popular Literature To Enhance Learning about Microbiology - Tracy O’Connor (American Society for Microbiology, 2019)
In order to stimulate engagement in microbiology, a reading-writing assignment based on a narrative popular science book was created for a one-semester introductory microbiology course. In order to encourage critical thinking, students were required to formulate a question related to the book to research and report on. Active learning was supported by guidance and feedback at each stage of the assignment. The assignment components were graded according to a rubric based on the learning outcomes: reading comprehension, question formulation, literature research, synthesis, and written communication. Median scores for the assignment components indicated that students successfully demonstrated the learning outcomes. A question was included on the final examination, asking students to summarize their most important learning from the assignment. Qualitative analysis of the exam answers revealed a wide variety of lessons learned about the practical applications of microbiology. On average, students scored better on the assignment and the assignment-related exam question than on the final exam. There was no significant correlation between a student’s performance on the final exam and their performance on either of the assignment-related assessments, suggesting that the assignment benefited students regardless of their exam-taking capability. According to surveys administered at the end of the introductory microbiology course and again when students were enrolled in a senior microbiology course, a strong majority of students found the reading-writing assignment to be engaging and informative. This assignment may be modified in various ways in order to suit the needs of other courses.